The Fourth Order Runge-Kutta Spreadsheet Calculator Using VBA Programing for Ordinary Differential Equations. (24th August 2015) - Tay, Kim Gaik; Kek, Sie Long; Cheong, Tau Han; Abdul-Kahar, Rosmila; Lee, Ming Foong
Abstract: Motivated by the previous literature works of spreadsheet solutions of ordinary differential equations (ODE) and a system of ODEs using fourth-order Runge-Kutta (RK4) method, we have built a spreadsheet calculator for solving ODEs numerically by using the RK4 method and VBA programming. In this spreadsheet calculator, a user interface input form is developed to capture the needed information to solve the ODE via the RK4 method. In the first frame of the user interface input form, users are prompted to enter independent and dependent variables in the ODE. On the other hand, they are needed to input the interval for the independent variables, initial value for the dependent variable, step size h and select the desired accuracy of calculation in the second frame of the user interface input form. Lastly, in the third frame of the user interface input form, users are required to enter the ODE function and exact function of ODE if it exists. Once the Solve button is clicked, the full solution of the ODE will be calculated automatically using the RK4 method. This spreadsheet calculator is user-friendly especially for users who are not familiar with Excel. We hope that this spreadsheet calculator can be used as a marking scheme for educators and students who require the full solutions of the ODEs. Moreover, this spreadsheet calculator reduces calculation time and it is hoped to improve students' learning ability.